0196 A Feasibility Study of Parents' Perceptions of close proximity in-situ Simulation within a Paediatric Cardiorespiratory Intensive Care Unit and Ward. (1st November 2014) - Lofton, Lydia; Gruendler, Kerstin; Combes, Julie; Lane, Mary; DeCosta, Kumi; West, Neil; Fossey, Dan; Desai, Ajay; Burmester, Margarita
Abstract : Background: Limited attention has been given to the challenge of providing family-centred care alongside simulations in the clinical area. 1 The validated 2 interprofessional in-situ SPRinT (Simulated Paediatric Resuscitation Team Training) programme delivers courses aimed at improving team performance and patient safety during critical events. We hypothesised that parents would actively support such training. Methodology: A prospective, cross-sectional survey of parents of inpatient children present during a SPRinT course was carried out Mar–May 2014. 2 h SPRinT courses consisted of didactic crisis resource management teaching, simulated scenario, and video-assisted debriefing by trained interprofessional faculty. Scenarios derived from real events (eg emergency resternotomy, catastrophic haemorrhage) have a full responding team using real equipment, medications and arrest calls. Parents completed anonymous questionnaires assessing perception of SPRinT courses and their effect. 13 quantitative questions with 0–100% score indicating level of agreement with statements and qualitative response. Level of agreement: >80% score=strong; <20%=weak. Results: 12 parents (6 fathers, 6 mothers; mean age 32 yrs, range 21–53 yrs) of 8 children (mean hospitalisation 47 days, range 1–270 days) returned questionnaires following 4 SPRinT courses. 1 questionnaire was excluded. 140/143 quantitative questions answered. Strong mean level of agreement scores were reported for: increased confidence in staff when they rehearse emergencies (97.3%), training should occur in all PICUs (97.3%), simulation may help staff provide safer care (96.4%). Weak mean level of agreement scores were reported for: perception of in-situ simulation to be disruptive/intimidating (4%), emergencies should be rehearsed elsewhere (5.5%), simulations upset me due to reminding me of what could happen to my child (19.1%), emergency simulations make me feel additional anxiety (19.1%). Qualitative analysis: "have seen the real thing on PICU, training definitely pays off". Conclusions: Parents felt simulations should occur in PICU, some reported mild increases in anxiety. Further research is required to determine specific provisions and information to mitigate anxiety. References: Patterson MD, Blike GT, Nadkarni VM. In Situ Simulation: Challenges and Results. In: Henriksen K, Battles JB, Keyes MA, et al ., editors. Advances in Patient Safety: New Directions and Alternative Approaches (Vol. 3: Performance and Tools). Rockville (MD): Agency for Healthcare Research and Quality (US); 2008 Aug Stocker M, Allen M, Pool N, et al . Impact of an embedded simulation team training programme in a paediatric intensive care unit: a prospective, single-centre, longitudinal study. Intensive Care Med . 2012;38(1):99–104